Taxonomic notes on some species of Euselasia Hübner, [1819] from the "Uriiformes" group, with the description of the immature stages of Euselasia satyroides Lathy, 1926, stat. rev. (Lepidoptera: Riodinidae: Euselasiinae) - Santos, Fabio Luis Dos; Dias, Fernando Maia Silva; Leite, Luis Anderson Ribeiro; Dolibaina, Diego Rodrigo; Casagrande, Mirna Martins; Mielke, Olaf Hermann Hendrik (Zootaxa, 2014)
The specific status of Euselasia satyroides Lathy, 1926, stat. rev., currently recognized as a synonym of Eurygona modesta Hewitson, 1856, is reinstated, and its immature stages, reared on Pouteria salicifolia (Sapotaceae), are thoroughly described and illustrated. The identity of some species of the genus Euselasia Hübner, [1819] belonging to the "Uriiformes" species group is clarified: lectotypes are designated to Eurygona eugeon Hewitson, 1856, Eurygona modesta Bates, 1868, Euselasia geon Seitz, 1913, and Euselasia satyroides Lathy, 1926, stat. rev.; Euselasia geon Seitz, 1913, syn. rev. is considered a synonym of Eurygona eugeon Hewitson, 1856. Additionally, a taxonomic dichotomous key for the species belonging to the "Uriiformes" group is provided.